If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 3(-12.9) = -23 Multiply 3 * -12.9 8x + -38.7 = -23 Reorder the terms: -38.7 + 8x = -23 Solving -38.7 + 8x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '38.7' to each side of the equation. -38.7 + 38.7 + 8x = -23 + 38.7 Combine like terms: -38.7 + 38.7 = 0.0 0.0 + 8x = -23 + 38.7 8x = -23 + 38.7 Combine like terms: -23 + 38.7 = 15.7 8x = 15.7 Divide each side by '8'. x = 1.9625 Simplifying x = 1.9625
| a-9=-20 | | 8-2x^2=x^2+4-7 | | 8(3+.08y)+3y=-23 | | 5/4-7/3c | | N^7=7 | | -3x+10y=1 | | 2c-8=-5c+4 | | 1/8x+3y=3 | | 5(3)-4(0)= | | x/2+5=18 | | 2x-(x+1)=-2 | | -3.7(x-5.3)-5.3(7x-2.4)=-53.35 | | 8(n+3)=9n+3-6 | | 39k^4-9k^3/4 | | 3/5(7x+11+6x) | | 8(3)+3(0)= | | (-2x+3)=25 | | -4(m+5)= | | 2+8j= | | 5x-4(0)=15 | | 9x-2=7x+34 | | 5(3+.08y)-4y=15 | | 6-9/6*3+5*3 | | -5=4x^2-x | | 3a-17=4 | | 6-9/6/3+5*3 | | 7p^2+7p-7=0 | | 175-6=6x+19 | | 3x+12x=105 | | 2(-2)+9(1)= | | 6-9*6/3+5*3 | | 8x+3(1)=-13 |